Teknik Bowing dalam Pembelajaran Praktek Instrumen Mayor (Gesek) di Prodi Pendidikan Musik Departemen Sendratasik UNP - Fela Vio Mimanda; Yensharti Yensharti (FBS Universitas Negeri Padang, 2022)
This study aims to explain the benefits orof thetechnique usesbowing in the practice course of major stringed instruments in the Music Education Study Program, Department of Drama, Faculty of Language and Arts, Padang State University. This type of research is qualitative with descriptive analysis method. The research instrument is the researcher himself. The object of research istechnique bowing in learning major string instruments 1 and 3 in music education study program FBS UNP. The research subjects were students of major string instruments 1 and 3, lecturers of major stringed instruments. Data collection techniques through literature study, observation, interviews and documentation. Data analysis techniques are data reduction, data presentation, and drawing conclusions. The results showed that the use of the Whole Bow (WB) had not been maximized because the strength of the index finger was not strong enough to push the swipe straighter or not controlled. The use of legato has not maximized the results because it has not been able to share the swipe as much because the strength on the index finger is not strong enough to control the swipe. The use of staccato has not maximized the results because a weak index finger in pushing the swipe and a stiff wrist cause friction to be less balanced. The use of spiccato has not maximized the results because the strength of the index finger that is not strong enough to push the friction causes the short length of friction to be less controlled to produce a shorter friction than the staccato. The use of legato staccato has not maximized the results because weak index strength and stiff wrists make friction not evenly distributed and staccato friction is less than optimal. The use of legato spiccato has not maximized the results because it is less able to produce a friction sound that is shorter than staccato due to the weak force on the index finger pushing the bow both up (Up Bow) and down (Down Bow).